Pengembangan Model Persediaan Single Vendor-Single Buyer dengan Lead Time Dapat Dikontrol - Wakhid Ahmad Jauhari (Performa: Media Ilmiah Teknik Industri, 2007)
In this paper we consider the single vendor-single buyer integrated inventory model. We relax the assumption of deterministic demand and assume that it is stochastic. We also consider the buyer’s lead time can be shortened at an extra crashing cost which depends on the lead time length to be reduced.We develop effective iterative procedures for finding the optimal policy.